Sobre los cómics, las historietas, las películas, las novelas y otras comiquitas ideológicas - Fernández, Oscar (Nómadas. Critical Journal of Social and Juridical Science, 2011)
The ideology dresses from the Marxist conception it suggests us that the same one is seen as false conscience and that in consequence, everything is I suspect of being read as ideology. Before this perspective there is no another alternative that her against ideology that in turn can turn into ideology when it is in use as mechanism of propaganda or as advertising instrument I marry The Simpsons. To this respect the comics are and have been ideological instruments that express the premeditation of a system, in this case the capitalism. In others, socialism and / or fascism.
Keywords: Marxism; ideology; against ideology; comics